Stability analysis of an expansive soil slope under heavy rainfall conditions with different anchor reinforcements - Yuqi Liu (Scientific Reports)
Abstract This study investigates the vulnerability of expansive soil slopes to destabilization and damage, particularly under intense rainfall, due to their heightened sensitivity to moisture. Focusing on a project in Yunnan Province, numerical simulation software is employed to address slope stability challenges. Meanwhile, the soil mechanical parameters of this study were acquired through experimentation. The analysis considers six conditions: unsupported, conventional anchor and stabilizing pile reinforcement, and NPR (Negative Poisson’s ratio) anchor and stabilizing pile reinforcement, evaluated under both normal and rainstorm conditions. The research outcomes reveal noteworthy insights: (1) The efficacy of NPR anchors in mitigating deformation in expansive soil landslides is investigated, broadening their application potential, particularly in restricting maximum slope displacement compared to conventional anchors. (2) No significant difference in safety factors for slope stability is observed between NPR and conventional anchors. Under rainstorm conditions, safety factors are 1.39 and 1.32 for NPR and conventional anchor and stabilizing pile support, respectively, while under normal conditions, they are 1.42 and 1.39. (3) The NPR anchor, in contrast to the conventional anchor, ensures a more uniform force distribution across the stabilizing pile. (4) While combined support structures contribute to slope stabilization, NPR anchors surpass conventional anchors in limiting slope displacement.